Concept And Typology of Discourse Personality - Hamdamova Dilafruz Malikjon kizi (Genius Publishing Group, 2022)
In modern linguistics, attempts to comprehend the concept of "linguistic personality", determine the structure and classify its models are widely represented. This is due to the fact that anthropocentrism today is the main characteristic feature of the paradigm of scientific humanitarian knowledge and human knowledge is impossible without learning the language. Cultural linguistics is one of the new and promising areas in linguistics, where the defining concept is “linguistic personality”.
Keywords: Linguistic; language; communicative; dialog